'Click here to share with a friend': a uses and gratifications approach to word-of-mouth marketing effectiveness. (1st January 2011) - Coyle, James R.; Smith, Ted; Lightfoot, Elizabeth; Neace, William; Platt, Glenn
The burgeoning interest in viral marketing and social media optimisation can be seen as a response to the growing and prohibitive clutter inherent in today's fragmented media landscape that leads to messages being attended to less reliably and exclusively. Research on predictors of viral marketing effectiveness is in its infancy, especially as it relates to the use of advertising as the primary vehicle for a viral campaign. We explore factors that prompt advertising sharing, and introduce a shareability scale, a tool to gauge the sharing potential of interactive marketing communications. Across a B2B and a B2C sample, we found remarkable similarity. Participants who were willing to share advertising information tended to be more mindful of others when processing the advertisement, to have a greater general tendency to share internet information, to be more highly involved in the product category, and, in the B2C sample, to be less concerned about source trustworthiness when passing along information found online. Implications for new media researchers and advertisers are discussed.